Two‐dimensional UTE overview imaging for dental application. Issue 5 (10th May 2020) - Stumpf, Kilian; Kaye, Elena; Paul, Jan; Wundrak, Stefan; Pauly, John M.; Rasche, Volker
Abstract : Purpose: To investigate the applicability of a 2D‐UTE half‐pulse sequence for dental overview imaging and the detection of signal from mineralized dental tissue and caries lesions with ultra‐short T 2 ∗ as an efficient alternative to 3D sequences. Methods: A modified 2D‐UTE sequence using 240‐µs half‐pulses for excitation and a reduction of the coil tune delay from the manufacturer preset value allowed for the acquisition of in vivo dental images with a TE of 35 µs at 1.5T. The common occurrence of out‐of‐slice signal for half‐pulse sequences was avoided by applying a quadratic‐phase saturation pulse before each half‐RF excitation. A conventional 2D‐UTE sequence with a TE of 750 µs, using slice selection rephasing, was used for comparison. Results: Quadratic phase saturation pulses adequately improve the slice profile of half‐pulse excitations for dental imaging with a surface coil. In vivo images and SNR measurements show a distinct increase in signal in ultrashort T 2 ∗ tissues for the proposed 2D‐UTE half‐pulse sequence compared with a 2D‐UTE sequence using conventional slice selection, leading to an improved detection of caries lesions. Conclusion: The proposed pulse sequence enables the acquisition of in vivo images of a comprehensive overview of bone structures and teeth of a single side of the upper and lower jaw and signal detection from mineralized dental tissues in clinically acceptable scan times.